Combining ability in Jatropha curcas L. Genotypes - Maftuchah, Maftuchah (Pakistan Academy of Sciences, 2017)
Jatropha curcas L. is a vegetable oil plant growing under diverse climates throughout the year. This plant can adapt to very low rainfall areas and marginal lands possessing low soil fertility, and could produce high biomass as a potential cover crop to reduce evaporation [1]. The J. curcas biodiesel has numerous advantages, such as: more environmental friendly due to its better emission, higher combustion efficiency, biodegradable, and renewable. Oil content in J. curcas is rather high which can be used to replace diesel fuel to some extent [2]. thus, the Jatropha biodiesel has the potential to increase an independent fuel supply [3]. In an attempt to provide biodiesel fuel in Indonesia, by the year 2025 the cultivation area under J. curcas is intended to be increased to about 2.4×106 ha; the available land area for the purpose in the country is a mostly dry and unproductive otherwise [4]. The Directorate General of Plantation has planned for J. curcas cultivation especially in West Nusa Tenggara, East Nusa Tenggara, Southeast Sulawesi, Gorontalo, Maluku, and Papua areas [5]. However, a desirable variety of J. curcas with high production potential and adaptability in such areas is not available as yet. The success of the breeding program to produce such a leading variety relies predominantly on the available germplasm. The potential of a good genotype source can be exploited through introduction, exploration and hybridization. In an effort for exploration of J. curcas during 2005, the Centre for Research and Plantation Development had collected 421 germplasm accessions from East Java, West Nusa Tenggara, East Nusa Tenggara, and South Sulawesi areas [6]. The variety improvement can be attempted by utilizing a proper germplasm source [8]. This research was conducted in the plantation of J. curcas’s germplasm located in Asembagus – Situbondo, East Java, Indonesia using seven local accessions of J. curcas, i.e., HS49, SP16, SP38, SP8, SM33, SP34, and SM35 [7].